Critical Review of Content Analysis Studies on Corporate Social Responsibility - Al-Giffari, Haekal Adha; Mayukh, Nafisa (MultiTech Publisher, 2024)
This critical review examines three selected papers that employed content analysis to investigate Corporate Social Responsibility (CSR) communication issues. The advantages of content analysis include non-reactivity, non-obtrusiveness, and the ability to conduct longitudinal studies using archive materials. However, it also suffers from time-consuming analysis, subjectivity in coding, and the disregard for context. The studies share a common focus on CSR communication issues and the utilization of content analysis. They highlight stakeholders' visibility, prominent CSR issues, and the tone of coverage in newspapers. Nonetheless, differences exist in the geographical scope and methodological transparency. In conclusion, content analysis offers valuable insights into CSR communication issues, but its limitations must be addressed. Future research should adopt systematic and transparent sampling and coding techniques, compare different newspapers and cultural contexts, and consider combining content analysis with other methods for a comprehensive understanding. Expanding research across various countries and considering cultural dimensions promises richer data and deeper insights into CSR framing by business newspapers.